An Interprofessional Team-Based Learning Module in Quality Improvement Concepts - Paul Haidet; Robert Cherry; Mary Beth Clark; Sandra O'Sullivan; Chengwu Yang (Association of American Medical Colleges, 2012)
Abstract Nurses and physicians share responsibility for improving quality and safety in health care systems, which argues for shared learning about these concepts. This 2.5-hour module, one of two on quality improvement (QI) principles, contains materials to use with first-year medical students and senior bachelor's degree nursing students. The module uses the team-based learning (TBL) method and assumes that users are familiar with TBL terminology and procedures. Included in the resource are a suggested time line, student preparation assignment, readiness assurance tests, application activities, and PowerPoint slides. Students are randomly assigned to learning teams, ensuring an even mix of nursing and medical students. Because our students are naive to TBL at the start, we conduct a warm-up readiness assurance test and a warm-up application activity to orient them to TBL processes. Both of these warm-up activities use brief introductory content about QI principles. We follow them with a more in-depth readiness assurance and application phase, which takes proportionately longer to complete. We use the PowerPoint mostly for timekeeping, orientation, and wrap-up points. It does not contain any unique content over that embedded in the readiness assurance and application materials. This module represents an initial attempt to combine TBL, interprofessional education, and QI concepts. TBL may provide an ideal method for teaching QI content in an interprofessional context because it requires students of various backgrounds to work together to solve real-world, application-based problems. Our hope is that by working together on such activities, nursing and medical students can learn how to build relationships across professional boundaries and see opportunities for improvement in the health care system. Although we have implemented this resource mainly with nursing and medical students, we feel that it may also be useful for a variety of other professional students, including physician assistants, pharmacists, nurse practitioners, and others.